Mobilização educativa em tempos de crise revolucionária. Periferia e centro no processo de democratização das escolas (1974-1976) - António Teodoro (Universidade do Minho, 2004)
The Portuguese Revolution of the 25th April 1974 allowed a social mobilization without precedents in the countrys history. In this paper, included in an event that pretends to commemorate 30 years of democratic schools government, the author reflects about the ways through which the school actors mobilization in the periphery (in particular, teachers and students) had influenced the centre, or, in other words, had constrained the political programmes (and the action) of the provisional governments. We argue that, in this period 1974-1976, power changed to the schools, which permitted a reformulation (and a remobilization) of the educational reform main goal, giving new dimensions to the democratic participation, equity, and the learning practices. These policies, yet inserted in an optimist context about schooling, had strengthened the education-democracy axle, that allowed, in a revolutionary time, mobilizing the actors and legitimating educational policies options.